La política consular en Estados Unidos: protección, documentación y vinculación con las comunidades mexicanas en el exterior - Cárdenas Suárez, Héctor (El Colegio de México A.C., 2019)
The consular policy of Mexico is a public policy of the state that responds to structural problems and opportunities in the relationship between Mexico and the United States, and which shows a strong continuity throughout recent governments. During the presidency of Peña Nieto, the consular policy responded to structural and sui generis problems related to the strong social and economic integration between the two countries, to the presence and specific challenges of the Mexican diaspora, and to the changing political conditions in the USA. Its general trend has been the gradual modernization of programs and services, and investment in the expansion of the consular network. Looking to the future, consular policy must continue to modernize and solve the challenge of limited resources.